SEDIMENT ORGANIC MATTER CONTENT AND MACROZOOBENTHOS ABUDANCE IN THE ESTUARY OF KAMBANG PESISIR SELATAN DISTRICT WEST SUMATERA - Putri, Rahmi Delima; Nedi, Syahril; Efriyeldi, Efriyeldi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2021)
Around the Kambang Estuary, there are fish shelters (TPI), fishing boat ports, residential areas, and mangrove ecosystems. This causes a decrease in water quality due to the increase in organic matter, which has an impact on the life of macrozoobenthos. The study conducted in February 2021 aims to analyze the organic matter content of sediments, identify the type and abundance of macrozoobenthos and the relationship between sedimentary organic matter and the abundance of macrozoobenthos. Determination of stations using purposive sampling method. This research was carried out at 4 stations with 4 sampling points. The results showed that the organic matter content found varied from 4.23 to 8.47%. The abundance of macrozoobenthos ranged from 13.89 to 38.89 ind/m2. The species of macrozoobenthos found at the study site consisted of 8 species from 3 classes of bivalves, gastropods and malacostraca. The relationship between the organic matter content in the sediment and the abundance of macrozoobenthos is obtained by the equation Y = 22.734 + 0.319X, where the coefficient of determination (R2) is 0.003 and the correlation coefficient (r) is 0.054, which is a very weak shows correlation.